Cultivation of Fetal Liver Cells in a Three-Dimensional Poly-L-Lactic Acid Scaffold in the Presence of Oncostatin M - Jinlan Jiang; Nobuhiko Kojima; Taisei Kinoshita; Atsushi Miyajima; Weiqun Yan; Yasuyuki Sakai (Cell Transplantation, 2002)
To investigate the feasibility of fetal liver cells for liver tissue engineering, the supporting function of poly-l-lactic acid (PLLA) for fetal liver cells and the effects of oncostatin M (OSM) on hepatic differentiation were studied. After preparing three-dimensional biodegradable PLLA scaffold having a well-developed open-pore structure by a gas-forming method with ammonium chloride particles as a porogen and a gas-forming reagent, fetal liver cells separated from E14.5-C57BL/6CrSlc murine embryos were inoculated in the PLLA scaffolds. Cells were cultured in Williams' E medium with or without OSM (10 ng/ml) for 30 days with a medium change every 2 days. Results showed that there were significant increases in the number of cells and in albumin secretion in PLLA culture compared with in monolayer culture on day 15. In addition, a significant increase in albumin secretion was observed in OSM-added PLLA culture compared with OSM-free culture, and there was only a slightly enhanced albumin secretion in monolayer cultures with OSM. These results suggest that PLLA may enhance the biological activity of OSM for inducing maturation of fetal liver cells. Interestingly, the number of cells in PLLA culture with OSM decreased compared with OSM-free PLLA culture at day 15. This may be because promotion of hepatic development by OSM simultaneously suppressed in vitro hematopoiesis (i.e., blood cell production). In summary, our results indicate that the three-dimensional PLLA scaffold is a good support material for the cultivation of fetal liver cells and that OSM is capable of not only terminating hematopoiesis of the fetal liver but also stimulating the maturation of hepatic parenchymal cells in vitro.